The perceptions of law students and teachers on the development of virtual legal academic activities - González Aguilar, Hugo (2023)
In the present work, he analyzes the perceptions of the main protagonists of the teaching-learning process in the context of virtuality: students and teachers. It is important to study the perceptions about the experiences, uncertainties or challenges about the learning processes mediated by ICTs. A qualitative analysis has been carried out based on the discourse of both participants. The main categories have been systematized: asynchronous, synchronous moment and the mastery of technological tools. It is concluded that the main actors are adapting to the process of virtual classes and show active participation, but they also show some difficulties such as the connectivity problem, the little time they have to develop various tasks; and, in some cases, the lack of mastery or knowledge of the digital tools and the virtual platform of the university.